Combined azelastine fluticasone nasal spray versus fluticasone propionate nasal spray in postoperative management of central compartment atopic disease (CCAD) - Elwany, Samy; Ibrahim, Ahmed Aly; Elwany, Mona; Tousson-Abouelazm, Nihad; Kholief, Amr (Frontiers in Pharmacology, 2026)
BackgroundCentral compartment atopic disease (CCAD) is a subtype of chronic rhinosinusitis with nasal polyps (CRSwNP), distinguished by polypoid changes in the middle turbinates, superior nasal septum, and/or superior turbinates.ObjectiveThe aim of this study was to compare the efficacy of combined azelastine/ fluticasone propionate spray (Azeflu) with fluticasone propionate nasal spray (FP) for management of CCAD after endoscopic sinus surgery.MethodsThe present work is a prospective, randomized, double-blinded study that included 48 patients, who underwent endoscopic surgery for refractory CCAD. The patients were randomly enrolled into two groups using simple randomization. Group A patients received FP (50 μg per spray) twice daily, while group B patients received Azeflu spray (137/50 μg, Aze/FP per spray) twice daily. Outcome measures included clinical assessment (SNOT-22), Lund Mackay radiologic score (LM), total serum IgE, nasal mucosa eosinophil count, and polyps score, and need for revision surgery. The results were collected before surgery as well as 6 and 12 months after surgery.ResultsSNOT-22 scores, total serum IgE, and nasal mucosa eosinophil count decreased significantly in both groups at the end of follow-up period. The decrease was significantly greater in group B patients who received the combined spray. On the other hand, there was a modest decrease in LM scores at 6 and 12 months after surgery in both groups. The frequency of polyps recurrence was significantly less in group B than in group A.ConclusionThe present research shows that nasal sprays may effectively reach the target areas in the central compartment after surgery, potentially benefiting from the widened post-surgical nasal corridor. Combined steroid/H1 blocker sprays provided better postoperative control of CCAD than steroid sprays. The synergistic action of H1 blockers in the combined sprays confirms the association between CCAD and nasal allergy and encourages us to consider it as a first line treatment for the disease.